Multiple-objective optimization of a methanol/diesel reactivity controlled compression ignition engine based on non-dominated sorting genetic algorithm-II. (15th September 2021) - Jing, Zheng; Zhang, Chunhua; Cai, Panpan; Li, Yangyang; Chen, Zhaoyang; Li, Songfeng; Lu, An
Highlights: Performance and emission characteristics of methanol/diesel RCCI are investigated. BTE and BS -emissions are analyzed and predicted as functions of BMEP, DIT and CCR . Pareto solutions between BTE and BS -emissions are obtained by using RSM and NSGA-II. Global Pareto solution is found at 0.855 MPa BMEP, −8 to −10 °CA DIT and 17–20% CCR . Abstract: To obtain a coordinating relationship between brake thermal efficiency ( BTE ) and brake specific ( BS ) emissions, methanol/diesel reactivity controlled compression ignition (RCCI) combustion was conducted on a modified heavy-duty diesel engine. The test results indicate that methanol/diesel RCCI exhibits different combustion characteristics under various operation strategies. Brake mean effective pressure ( BMEP ) and co-combustion rate ( CCR ) have a statistical trade-off impact on BTE and BS -emissions. With the increase of BMEP, BTE increases, BSCO and BSHC decrease but BSNOx overall increases. Also, low BSNOx but deteriorative BTE, BSCO and BSHC are observed with the increase of CCR . Moreover, with the advance of diesel injection timing ( DIT ) from ATDC to BTDC, maximum BTE first increases then decreases, BSCO and BSHC overall increase, and BSNOx overall first decreases then increases. Subsequently, three input parameters including BMEP, DIT and CCR are optimized to maximize the BTE and minimize the gas BS -emissions based on response surface methodology (RSM) and non-dominated sorting genetic algorithm-II (NSGA-II). The predicted results show that this methanol/diesel RCCI engine could achieve a globally optimized goal at 0.855 MPa BMEP, nearly 8–10 °CA BTDC DIT and 17–20% CCR with BTE, BSCO, BSHC and BSNOx being 40.5%, 1.25, 0.15 and 1.66 g/kW·h, respectively. Moreover, it could also obtain a partial optimization at 0.48–0.60 MPa BMEP, nearly 5–10 °CA BTDC DIT and 16% CCR with accepted range of BTE and BS -emissions.